Reimagining the Mandaluyong Correctional Institution for women into a humane and rehabilitative vertical prison development - Molina, Mika Nadine S. (College of Architecture, University of the Philippines Diliman, 2025)
The increasing incarceration rates globally and in the Philippines have highlighted critical challenges within correctional systems, particularly for female Persons Deprived of Liberty (PDLs). The Correctional Institution for Women (CIW) in Mandaluyong, the only female penal institution in the Philippines, operates at over double its intended capacity, resulting in overcrowded conditions that hinder the provision of adequate services, privacy, and rehabilitation opportunities. These conditions worsen the challenges faced by female PDLs, affecting their well-being and reintegration into society. This study proposes a vertical prison development inspired by the Panoptic principle, reimagining centralized visibility as a tool for rehabilitation rather than control. Moving away from an oppressive surveillance model, the design prioritizes dignity, privacy, and trauma-informed care, ensuring a structured yet supportive environment that fosters security, rehabilitation, and reintegration. The layout is guided by a centralized core, with programmatic spaces strategically organized to separate security levels, rehabilitation zones, and communal areas, balancing oversight with autonomy. This study advocates for a shift from punitive to reformative approaches in the Philippine correctional system. The model offers a solution to urban space constraints while serving as a prototype for humane and inclusive correctional facilities. Ultimately, this project contributes to the discourse on gender-sensitive prison design and supports the broader goal of creating equitable environments that uphold the dignity and rights of incarcerated women.